KOSAKATA KELUARGA DALAM BAHASA PRANCIS ISYARAT - Siti Romla W.A,; Irianty Bandu, (JOEL: Journal of Educational and Language Research, 2022)
This research is entitled "Vocabulary of Families in French Sign Language". The purpose of this study are to determine the stages in each gesture in signaling the family vocabulary in French sign language, knowing the pattern of sign language formation with the signs represented, and knowing the peculiarities contained in French sign language. This research used qualitative research methods. In this case, the writer uses Le Dico Elix dictionary in short videos with an average duration of 3 seconds in collecting the data. In the research, the writer used the theoretical basic of semiotics with the concept of the triangle of meaning proposed by Charles Sanders Peirce. Based on the analysis, the research shows that there are three types of vocabulary signs for family sign, namely alphabetical signs, physical characters, and activities. Then, the peculiarities of the movements used in the pattern of family sign formation.